2015
DOI: 10.1128/jvi.03659-14
|View full text |Cite
|
Sign up to set email alerts
|

Insect Inhibitor-of-Apoptosis (IAP) Proteins Are Negatively Regulated by Signal-Induced N-Terminal Degrons Absent within Viral IAP Proteins

Abstract: Inhibitor-of-apoptosis (IAP) proteins are key regulators of the innate antiviral response by virtue of their capacity to respond to signals affecting cell survival. In insects, wherein the host IAP provides a primary restriction to apoptosis, diverse viruses trigger rapid IAP depletion that initiates caspase-mediated apoptosis, thereby limiting virus multiplication. We report here that the Nterminal leader of two insect IAPs, Spodoptera frugiperda SfIAP and Drosophila melanogaster DIAP1, contain distinct insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 67 publications
1
40
0
Order By: Relevance
“…We made a similar observation: DIAP1 decreased in S2 cells after DCV infection. The same research group recently reported another mechanism for the degradation of DIAP1 that is independent of Reaper, Hid, and Grim (66). Therefore, it is important to elucidate the mechanism by which the productive infection of DCV brings about a reduction in the level of this caspase inhibitor for the induction of apoptosis in Drosophila cells.…”
Section: Discussionmentioning
confidence: 99%
“…We made a similar observation: DIAP1 decreased in S2 cells after DCV infection. The same research group recently reported another mechanism for the degradation of DIAP1 that is independent of Reaper, Hid, and Grim (66). Therefore, it is important to elucidate the mechanism by which the productive infection of DCV brings about a reduction in the level of this caspase inhibitor for the induction of apoptosis in Drosophila cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as expected for critical regulators of cell death, SfIAP and DIAP1 are highly responsive to host degradative signals (8,21,(27)(28)(29)(30)(31). Consequently, factors that positively or negatively affect IAP levels modulate apoptosis, including that triggered by virus infection.…”
Section: Importancementioning
confidence: 99%
“…Similarly, SfIAP and Op-IAP3 also exist as homodimeric complexes, which can be dominantly inhibited by various truncations of the same (8,11). Viral Op-IAP3, which lacks a degron-containing leader, is highly stable and resistant to signal-induced turnover (27). It inhibits apoptosis in baculovirus-infected Spodoptera cells, acting at a step upstream of initiator caspase activation (34)(35)(36)(37).…”
Section: Importancementioning
confidence: 99%
See 2 more Smart Citations